Utopia First! A Machiavellian Conception of Solidarity in More's Utopia - Phélippeau, Marie-Claire (2018)
This paper shows how solidarity is one of the founding principles in Thomas More's Utopia (1516). In the fictional republic of Utopia described in Book II, solidarity has a political and a moral function. The principle is at the center of the communal organization of Utopian society, exemplified in a number of practices such as the sharing of farm work, the management of surplus crops, or the democratic elections of the governor and the priests. Not only does solidarity benefit the individual Utopian, but it is a prerequisite to ensure the prosperity of the island of Utopia and its moral preeminence over its neighboring countries. However, a limit to this principle is drawn when the republic of Utopia faces specific social difficulties, and also deals with the rest of the world. In order for the principle of solidarity to function perfectly, it is necessary to apply it exclusively within the island or the republic would be at risk. War is not out of the question then, and compassion does not apply to all human beings. This conception of solidarity, summed up as “Utopia first!,” could be dubbed a Machiavellian strategy, devised to ensure the durability of the republic. We will show how some of the recommendations of Realpolitik made by Machiavelli in The Prince (1532) correspond to the Utopian policy enforced to protect their commonwealth.
Keywords: Le Prince; Machiavel; Machiavelli; Realpolitik; The Prince; Thomas More; Utopia; Utopie; Solidarity; Solidarité